Design and implementation of a testing platform for ship control: A case study on the optimal switching controller for ship motion. (April 2023) - Wang, Le; Li, Shijie; Liu, Jialun; Hu, Yuanchao; Wu, Qing
Abstract: Fully autonomous navigation is the highest level of ship autonomy, which has high requirements for the adaptability of the ship control system. Taking navigation with large turning errors as an example, this paper combines the intelligent optimization controller with the traditional controller and adopts the controller switching strategy to guide the ship's path following. In order to illustrate the feasibility of optimizing the switching mode of the motion controller to reduce the large turning error during ship navigation, this paper designs a test platform for the intelligent navigation of the model ship, and tests the effect of the optimal switching strategy of the controller. Firstly, the structure of the intelligent ship system is analyzed, and the framework of the intelligent navigation system is emphasized. Secondly, based on the analysis of the characteristics of controllers, the optimal switching strategy of the motion controller is proposed. Then, the construction process of the testing platform is described. Finally, the optimal switching strategy of the motion controller is verified on this test platform for the case of a large turning error of the ship. The results show that the implementation of the switching strategy can effectively reduce the control error compared with the mode without using the strategy. The experiment extends the ship motion control mode strategically and improves the adaptability of ship motion control. Based on the testing platform, this experiment can simulate the process of the control system autonomously selecting an appropriate controller according to the ship's motion state and navigation scenarios, which is helpful to enhance the adaptability of the ship in the face of special navigation scenarios. Highlights: The structure and design process of ship testing platform is described.. Research process of optimal switching strategy for control are summarized. A combined optimal switching controller of ship motion is designed. A new method is proposed to reduce the large turning error of ships during navigation.